Gideon Denison letterbooks - Denison, Gideon, 1753-1799.
Letterbooks of the business of Gideon Denison kept by his brother, Ezra Denison, in Savannah, Ga. Also includes records of tickets for the Savannah Lottery of 1793.
Handwritten transcripts.
Merchant; resident of Sion Hill, Md.
Collection material in English.
Forms part of: Miscellaneous Manuscripts collection.
Keywords: Lotteries -- Georgia -- Savannah; Savannah (Ga.) -- Commerce; Merchants